Influence of Maillard reaction conditions and solvent extraction on the surface activity and foaming characteristics of black cumin protein concentrates - (:unkn) unknown (SPRINGER INDIA, 2021)
Cold press manufacture of black cumin (BC) oil leads to the formation of BC press cakes that contain significant amounts of protein. Here, an attempt was made to enhance the functionality of BC protein concentrates obtained from cakes based on Maillard conjugation using 3 different of carbohydrates. Molecular weight distribution of the conjugates was determined via electrophoretic techniques. The extent of carbohydrate binding was measured by RP-HPLC-RID. Surface activity and elasticity was studied using drop shape tensiometry. The extent of glucose binding accounted for up to 85% for a protein:glucose ratio of 1:2. Foaming capabilities were moderately enhanced due to Maillard conjugation in the absence of solvent extraction, while due to solvent induced partial denaturation, further enhancement of foaming performance took place. Furthermore, sugar binding capabilities were enhanced upon solvent treatment, while surface pressure and foaming capacity were not necessarily improved. Adsorption rate at the air-water surface and dilational elasticity was highly dependent on molecular size of reacting sugars. In addition, oil remaining in the samples also had a bearing on the extent of Maillard conjugation. Consequently, tailoring of processing conditions could enhance foaming characteristics of BC proteins and ensure their utilization in food foams and other food dispersions.
Keywords: Black cumin protein concentrates; Maillard conjugation; Surface activity; Foaming capacity; Drop shape tensiometry; FT-IR spectroscopy; FUNCTIONAL-PROPERTIES; SECONDARY STRUCTURE; REACTION-PRODUCTS; MODEL SYSTEM; EMULSION; GLUCOSE; PEA